EFEKTIVITAS PENGGUNAAN PERPUSTAKAAN BERBASIS DIGITAL DI SMA PEMBANGUNAN LABORATORIUM UNP - Shalsabila Irmanda; Hade Afriansyah; Hadiyanto Hadiyanto; Widiawati Widiawati (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to describe the effectiveness of digital library utilization at SMA Pembangunan Laboratorium UNP in terms of ease of use/access, system quality, user satisfaction, and the completeness of digital collections. Methods: This study employed a quantitative descriptive approach. The population consisted of 342 students of SMA Pembangunan Laboratorium UNP, with a sample of 79 students selected using the Stratified Random Sampling technique. Data were collected through a Likert-scale questionnaire that had met validity and reliability requirements and were analyzed using descriptive statistics by calculating the mean score. Results: The findings revealed that the effectiveness of digital library utilization was categorized as effective, with an overall mean score of 3.95. User satisfaction obtained the highest mean score (4.02), followed by ease of use/access (3.98), completeness of digital collections (3.97), and system quality (3.82). These findings indicate that the digital library has effectively supported students’ learning needs through accessible information services, adequate digital collections, satisfactory system performance, and positive user experiences. Novelty: This study provides a comprehensive assessment of digital library effectiveness at the secondary school level by integrating four key indicators—ease of use/access, system quality, user satisfaction, and completeness of digital collections—within a single framework of analysis.